Long-Term Efficacy of Occipital Nerve Stimulation for Medically Intractable Cluster Headache. Issue 2 (28th September 2020) - Leplus, Aurélie; Fontaine, Denys; Donnet, Anne; Regis, Jean; Lucas, Christian; Buisset, Nadia; Blond, Serge; Raoul, Sylvie; Guegan-Massardier, Evelyne; Derrey, Stéphane; Jarraya, Bechir; Dang-Vu, Bich; et al.
Abstract: BACKGROUND: Occipital nerve stimulation (ONS) has been proposed to treat refractory chronic cluster headache (rCCH) but its efficacy has only been showed in small short-term series. OBJECTIVE: To evaluate ONS long-term efficacy in rCCH. METHODS: We studied 105 patients with rCCH, treated by ONS within a multicenter ONS prospective registry. Efficacy was evaluated by frequency, intensity of pain attacks, quality of life (QoL) EuroQol 5 dimensions (EQ5D), functional (Headache Impact Test-6, Migraine Disability Assessment) and emotional (Hospital Anxiety Depression Scale [HAD]) impacts, and medication consumption. RESULTS: At last follow-up (mean 43.8 mo), attack frequency was reduced >50% in 69% of the patients. Mean weekly attack frequency decreased from 22.5 at baseline to 9.9 ( P < .001) after ONS. Preventive and abortive medications were significantly decreased. Functional impact, anxiety, and QoL significantly improved after ONS. In excellent responders (59% of the patients), attack frequency decreased by 80% and QoL (EQ5D visual analog scale) dramatically improved from 37.8/100 to 73.2/100. When comparing baseline and 1-yr and last follow-up outcomes, efficacy was sustained over time. In multivariable analysis, low preoperative HAD-depression score was correlated to a higher risk of ONS failure. During the follow-up, 67 patients experienced at least one complication, 29 requiring an additional surgery: infection (6%), lead migration (12%) or fracture (4.5%), hardware dysfunction (8.2%), and local pain (20%). CONCLUSION: Our results showed that long-term efficacy of ONS in CCH was maintained over time. In responders, ONS induced a major reduction of functional and emotional headache-related impacts and a dramatic improvement of QoL. These results obtained in real-life conditions support its use and dissemination in rCCH patients. Graphical Abstract: